Toleransi dalam Komunikasi Antarumat Beragama Perspektif Hadis - Robeet Thadi; Aan Supian (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2023)
Inter-religious communication cannot actually be separated from the role of Rasulullah SAW who sparked the idea of the Medina Charter. This article aims to describe in terms of hadith analysis about tolerance in interreligious communication using the keywords samhan samahah. Using a qualitative descriptive-analytical method approach, in particular, the descriptive-analytical method in this study used the takhrij method of hadith criticism studies (naqd al-hadith). Data collection techniques through library research, primary data through the application of the Hadith of the Book of 9 Imams and secondary data from literature related to the research topic. Data analysis techniques are taken through the stages of inventory, classification, and interpretation. The results of the study found two relevant hadiths about tolerance narrated by Ahmad Hadith No. 2003 and No. 24771, shows that the status of the validity of the hadith narrated by Ahmad No. 2003 regarding tolerance is considered as hasan li ghairihi, that the hadith narrated by Ahmad No. 2003 is maqbul ma'mul bih to be used as a basis for the actualization of religious tolerance in the era of contemporary life